Rocket Observation of Sub‐Relativistic Electrons in the Quiet Dayside Auroral Ionosphere. Issue 7 (6th July 2021) - Namekawa, T.; Mitani, T.; Asamura, K.; Miyoshi, Y.; Hosokawa, K.; Ogawa, Y.; Saito, S.; Hori, T.; Sugo, S.; Kawashima, O.; Kasahara, S.; Nomura, R.; et al.
Abstract: An energy spectrum of electrons from 180 to 550 keV precipitating into the dayside polar ionosphere was observed under a geomagnetically quiet condition (AE ≤ 100 nT, Kp = 1‐). The observation was carried out at 73–184 km altitudes by the HEP instrument onboard the RockSat‐XN sounding rocket that has been launched from Andøya, Norway. The observed energy spectrum of precipitating electrons follows a power law of −4.9 ± 0.4 and the electron flux does not vary much over the observation period (∼274.4 s). A nearby ground‐based VLF receiver observation at Lovozero, Russia shows the presence of whistler‐mode wave activities during the rocket observation. A few minutes before the RockSat‐XN observation, POES18/MEPED observed precipitating electrons, which also suggest whistler‐mode chorus wave activities at the location close to the rocket trajectory. A test‐particle simulation for wave‐particle interactions was carried out using the data of the Arase satellite as the initial condition which was located on the duskside. The result of the simulation shows that whistler‐mode waves can resonate with sub‐relativistic electrons at high latitudes. These results suggest that the precipitation observed by RockSat‐XN is likely to be caused by the wave‐particle interactions between whistler‐mode waves and sub‐relativistic electrons. Plain Language Summary: Sub‐relativistic electrons precipitating into the Earth's dayside polar ionosphere are observed by a sounding rocket under geomagnetically quiet conditions. An energy spectrum of these electrons in an energy range from 180 to 550 keV is reported at the rocket altitude. A possible mechanism for generating this precipitation is the resonance scattering of electrons by whistler‐mode waves, which we conducted a test‐particle simulation based on the ground and satellite observations. Key Points: A sounding rocket observed an energy spectrum of sub‐relativistic electron precipitation in the dayside polar ionosphere during quiet time Ground and satellite observations suggest that the precipitation observed by RockSat‐XN was caused by the whistler‐mode waves A test‐particle simulation for wave‐particle interactions based on the data of the Arase satellite supports the RockSat‐XN observation